CONTENT AND ANALYSIS OF THE ORGANIZATION OF THE OLYMPIAD IN BIOLOGICAL SCIENCES IN THE 2023-2024 ACADEMIC YEAR (III stage) - Zayniyev Suxrobjon Islombek o‘g‘li (Journals Park Publishing, 2023)
This article covers information about the state and analysis of the organization of the Biology Olympiad. The purpose and objectives of the Olympiad and the methodology for solving some written work questions at stage III were also shown.
Keywords: continuous education system, Olympiad, Pearson, Fisher, x2 method, null hypothesis, chemistry, biology, physics, microsporatite, megasporatite, microspore, megaspore.